The Contribution of Socio-Demographic Factors to Walking Behavior Considering Destination Types; Case Study: Temuco, Chile - Mohammad Paydar; Asal Kamani Fard (Social Sciences, 2021)
The improvement of walking contributes to maintain the minimum rate of physical activity and therefore the residents’ public health. This is while the amount of walking in daily transport of inhabitants has significantly decreased during the last decades in Temuco, Chile. In addition, the impact of socio-demographic as well as social factors on the improvement of walking behavior has been paid less attention in previous studies. This study aims to examine the contribution of socio-demographic factors and the active family environment to walking behavior as well as walking level based on three types of destinations in Temuco. The results of “Encuesta Origin Destino” (EOD) in Temuco were used to examine the objectives. It was found that a high percentage of people who walk in Temuco belong to low-income families. Moreover, most of the people who walk, do not have a driver’s license nor private cars in their household. Certain socio-demographic factors such as age, gender, driver’s license, private cars, and access to TV were found to have associations with overall walking behavior as well as walking level depending on three different destination types. Furthermore, the correlation was found between walking behavior and active family environment. These findings were discussed and their implications were addressed as well.